EMPLOYEE PERFORMANCE AS THE IMPACT OF TRANSFORMATIONAL LEADERSHIP AND JOB SATISFACTION IN PT ANUGERAH BARU DENPASAR - Fransisca Andreani; Abelio Petrik (Jurnal Manajemen dan Kewirausahaan, 2016)
PT Anugerah Baru in Denpasar has applied transformational leadership since 2014 so that employees feel more secure and motivated. Thus, it increases their performance. This study is undertaken to find the impact of transformational leadership on job satisfaction using employee performance as a mediating variable in PT. Anugerah Baru Denpasar using Partial Least Square (PLS). The results show that there is a positive and significant impact of transformational leadership on job satisfaction, a positive but insignificant impact of job satisfaction on employee performance, and a positive and significant impact of transformational leadership on employee performance.